2010
DOI: 10.1007/s00198-010-1467-z
|View full text |Cite|
|
Sign up to set email alerts
|

Sunlight and dietary contributions to the seasonal vitamin D status of cohorts of healthy postmenopausal women living at northerly latitudes: a major cause for concern?

Abstract: These longitudinal data show significant regional and ethnic differences in UVB exposure and vitamin D status for postmenopausal women at northerly latitudes. The numbers of women who are vitamin D deficient is a major concern and public health problem.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
149
2
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 158 publications
(170 citation statements)
references
References 46 publications
13
149
2
3
Order By: Relevance
“…Such an assumption can be drawn from the results of the study by Webb, Kline and Holick (1988) in which sunlight exposure was insufficient for vitamin D synthesis both in Boston (42.2°N) and Edmonton (52°N) from October to April [20]. On the other hand, in another study, a six degree latitude difference (Scotland, 51° and 57°) was associated with significant 25(OH)D concentration differences both in winter and summer [25].…”
Section: Prace Oryginalnementioning
confidence: 99%
“…Such an assumption can be drawn from the results of the study by Webb, Kline and Holick (1988) in which sunlight exposure was insufficient for vitamin D synthesis both in Boston (42.2°N) and Edmonton (52°N) from October to April [20]. On the other hand, in another study, a six degree latitude difference (Scotland, 51° and 57°) was associated with significant 25(OH)D concentration differences both in winter and summer [25].…”
Section: Prace Oryginalnementioning
confidence: 99%
“…39 The Azorean Archipelago is located in the middle of the Northern Hemisphere of the Atlantic Ocean and extends along a west-northwest to east-southeast orientation (between 36.5-43° N and 24.5-31.5° W); therefore, the amount of ultraviolet-B radiation might be insufficient for synthesizing vitamin D. Nevertheless, it has been argued that in fall and winter, diet provided proportionally more vitamin D because of the lack of ultraviolet-B radiation. 40 In addition, limited exposure to sunlight due to cultural and lifestyle practice may also play a part in etiology of vitamin D deficiency. It is reported that in healthy Caucasian adolescent boys aged 16-18 years, there was a significant association between sports-related sun exposure and vitamin D status.…”
Section: Discussionmentioning
confidence: 99%
“…Biochemical Measurements: Fasting blood samples were collected and serum Vitamin D was measured by ELISA method 13 . Plasma glucose was measured by using Glucose oxidasePeroxidase (GOD-POD) method 14 , (Auto analyzerolympus AU-200), Insulin concentration was measured by using Fluorescent Enzyme Immuno Assay( FEIA) and Insulin resistance was calculated by using HOMA-IR (insulin(μg) glucose(mg) 15 .…”
Section: Bmi= Weight In Kg ------------------Height In Mmentioning
confidence: 99%